2002
DOI: 10.1515/cclm.2002.157
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Rate of False-Positive Cultures of Mycobacterium tuberculosis in a Laboratory with a High Culture Positivity Rate

Abstract: Our laboratory, engaged in a prospective study of adult pulmonary tuberculosis, processed on average 1186 sputum samples per year for the detection of Mycobacterium tuberculosis (M. tuberculosis). Approximately 55% of all sputum samples were culture-positive. The study protocol required that all patients had their M. tuberculosis isolates DNA fingerprinted at diagnosis, and at subsequent time points if the patients either failed treatment or presented again with tuberculosis. Over a 22-month period, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In another published study, a South-African laboratory reported data representing a laboratory with a very high FPR and PSP[6]. In that study an average of 1186 culture samples per year were tested in the laboratory of which 55% were culture positive (PSP = 0.55, p = 1186 * 0.55 = 652).…”
Section: Resultsmentioning
confidence: 99%
“…In another published study, a South-African laboratory reported data representing a laboratory with a very high FPR and PSP[6]. In that study an average of 1186 culture samples per year were tested in the laboratory of which 55% were culture positive (PSP = 0.55, p = 1186 * 0.55 = 652).…”
Section: Resultsmentioning
confidence: 99%
“…Positive cultures were subcultured on Löwenstein-Jensen slants for genotyping by the standardized restriction fragment length polymorphism methodology based on the IS6110 transposable element (40). Standard protocols were in place to prevent cross contamination (6). Isolates were assigned to specific genotype families according to the specific IS6110 banding pattern (fingerprint).…”
Section: Methodsmentioning
confidence: 99%
“…The species from these positive MGIT cultures were then determined by standard PCR (4). Negative controls were included with each batch of clinical specimens processed to monitor for laboratory cross-contamination, as recommended elsewhere (1,21). Solid LJ slants were incubated at 37°C and were examined weekly for 6 weeks or until colonies became visible.…”
Section: Methodsmentioning
confidence: 99%